Enolase isoenzymes in the cerebrospinal fluid of patients with diseases of the nervous system. Issue 11 (November 1983) - Royds, J A; Davies-Jones, G A; Lewtas, N A; Timperley, W R; Taylor, C B
Abstract : Alpha and gamma enolase isoenzymes have been studied in 212 patients with a variety of neurological diseases. The results show that these proteins are sensitive markers of tissue damage which enable a distinction to be made between the involvement of glial and neuronal components.